From extraction to application: nanoemulsified lemongrass oil for biofilm and spore control in food preservation - Mohd Daud, Ili Syuhada; Mahmud Ab Rashid, Nor Khaizura; Palmer, Jon; Flint, Steve (Elsevier B.V., 2026)
Bacillus cereus is a spore-forming, toxin-producing pathogen that poses a persistent threat to global food safety due to its resistance to heat, disinfectants, and its ability to form biofilms. This review highlights the antimicrobial potential of lemongrass essential oil (LEO) and its major compound, citral, from traditional use to its modern application through nanoemulsion systems. It critically examines how extraction methods affect citral content and bioactivity, and how nanoemulsification enhances LEO's stability, solubility, and efficacy against B. cereus spores and biofilms. Applications include dairy, meat, and fresh produce preservation, where LEO-based coatings, packaging, and sanitizers offer clean-label alternatives to synthetic preservatives. The review also explores regulatory and safety concerns and identifies gaps in sensory effects, long-term stability, and dosing optimization. Overall, citral-rich LEO nanoemulsions represent a promising, sustainable strategy to improve microbial safety and shelf life in food systems affected by B. cereus .